Design considerations for rapid biodiversity reconnaissance surveys and long‐term monitoring to assess the impact of wildfire. (20th October 2021) - Southwell, Darren; Legge, Sarah; Woinarski, John; Lindenmayer, David; Lavery, Tyrone; Wintle, Brendan
Abstract: Aims: Reconnaissance surveys followed by monitoring are needed to assess the impact and response of biodiversity to wildfire. However, post‐wildfire survey and monitoring design are challenging due to the infrequency and unpredictability of wildfire, an urgency to initiate surveys and uncertainty about how species respond. In this article, we discuss key design considerations and quantitative tools available to aid post‐wildfire survey design. Our motivation was to inform the design of rapid surveys for threatened species heavily impacted by the 2019–2020 fires in Australia. Location: Global. Methods: We discuss a set of best practice design considerations for post‐wildfire reconnaissance surveys across a range of survey objectives. We provide examples that illustrate key design considerations from post‐fire reconnaissance surveys and monitoring programmes from around the world. Results: We highlight how the objective of post‐fire surveys drastically influences design decisions (e.g. survey location and timing). We discuss how the unpredictability of wildfire and uncertainty in the response of biodiversity complicate survey design decisions. Main conclusions: Surveys should be conducted immediately following wildfire to assess the impact on biodiversity, to ground truth fire severity mapping and to provide a benchmark from which to assess recovery. Where possible, surveys should be conducted at burnt and unburnt sites in regions with historical data so that state variables of interest can be compared with baseline estimates (i.e. BACI design). This highlights the need to have long‐term monitoring programmes already in place and be prepared to modify their design when wildfires occur. There is opportunity to adopt tools from statistics (i.e. power analysis) and conservation planning (i.e. spatial prioritization) to improve survey design. We must anticipate wildfires rather than respond to them reactively as they will occur more frequently due to climate change.